ANALISA PERAN SUMBER DAYA MANUSIA DALAM MANAJEMEN OPERASIONAL TERHADAP KOPERASI PP.NURUL JADID - Fahrudin, Fahrudin; Sunaika, Sunaika; Fitri, Maulidatul (KEADABAN: Jurnal Sosial dan Humaniora, 2022)
This research was conducted to find out how the analysis of the role of human resources in operational management on PP.Nurul Jadid cooperatives. The method that the researcher uses is descriptive qualitative method which uses interviews and observation methods. The results of the research obtained by the researcher indicate that the role of operational management on human resources has basically been done well or has been maximized, but in the supervision and planning of the role of human resources in evaluating it still has to be considered because there is no feedback between employees and employees. leader at work, and the planning is still less productive.